Beyond the Rebel Girl : Women and the Industrial Workers of the World in the Pacific Northwest, 1905-1924 - Mayer, Heather (Book collections on Project MUSE., 2018)
"A history of Pacific Northwest women's roles in the Industrial Workers of the World organization between 1905 and 1924"--